Acoustic identification of insectivorous bats in southern Thailand - Sara Bumrungsri (Prince of Songkla University, 2022)
Acoustic identification of free flying bats is a vital component of acoustic bat survey using bat detector which is increasing popular in studying distribution, activity level, habitat use of a particular insectivorous species or bat community. This study has objectives to establish the comprehensive reference collection of call recorded by time expansion bat detector, and to determine the performance of Discriminant Function Analysis in identification of bat echolocation call in species-rich bat community of southern Thailand. A large reference collection of calls (>1500) were established together with voucher specimens in Princess Maha Chakri Siridhorn Natural History Museum. 187 calls from 26 species of insectivorous bats using frequency modulated call (FM) and 380 Calls of 19 species of bats using constant frequency call (CF) recording via time expansion bat detectors were examined. Call duration, frequency at maximum energy, frequency at half of the call’s duration, frequency at the beginning of call, highest frequency in that harmonic, minimum frequency and interpulse interval were determined from each call, mostly each call is from one bat. DFA was applied to identify these calls to species. Within FM bats, DFA correctly classified 79.1% of calls. After subdivision of FM calls to those bats with quasi-constant frequency and bats withsteep FM, DFA resulted in 97.6% and 69.9% correctly identified, respectively. For Myotis, DFA correctly classified 100% of calls. For bats using constant frequency, 76.3 % was correctly identified with DFA. Practically, division field recorded calls into call types will improve percent of correct identification in DFA in certain bat groups. Taxonomic clarification is urgently needed in Miniopterus. Geographical variation in call frequency make their call identification less accurate, even in CF bats, and further study should be done to explore such pattern.